2022
DOI: 10.1021/acsabm.2c00520
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Nanoparticle Heteroaggregates as Stabilizers of Pickering Emulsions for Vitamin D3 Efficient Delivery

Abstract: Vitamin D3 deficiency is a major public health problem worldwide, and standard cholecalciferol formulations provide poor absorbability of the vitamin. Several biphasic formulas have been proposed to overcome the disadvantages in which Pickering emulsions stand out in particular. This paper describes olive oil-in-water Pickering emulsions stabilized by pseudoboehmite (AlOOH), cellulose nanocrystals (CNC), and their heterocoagulates. Colloidal properties were assessed by laser Doppler microelectrophoresis, poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…To stabilize such a system, the use of emulsifiers is required, which can be surfactants (classical emulsions) or solid particles (Pickering emulsions). Unlike classical emulsions, Pickering emulsions are more stable to coalescence and can be stabilized with edible or less toxic solids such as those from natural proteins and polysaccharides, inorganic particles, and hybrid organic–inorganic systems. , Another advantage of Pickering emulsions is the ability in some cases to maintain or completely restore the emulsion state after partial removal of the continuous phase . Due to their excellent properties, Pickering emulsions are currently used in pharmaceutical engineering, food processing, drug delivery, cosmetics, agriculture, oil production, and material synthesis. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To stabilize such a system, the use of emulsifiers is required, which can be surfactants (classical emulsions) or solid particles (Pickering emulsions). Unlike classical emulsions, Pickering emulsions are more stable to coalescence and can be stabilized with edible or less toxic solids such as those from natural proteins and polysaccharides, inorganic particles, and hybrid organic–inorganic systems. , Another advantage of Pickering emulsions is the ability in some cases to maintain or completely restore the emulsion state after partial removal of the continuous phase . Due to their excellent properties, Pickering emulsions are currently used in pharmaceutical engineering, food processing, drug delivery, cosmetics, agriculture, oil production, and material synthesis. , …”
Section: Introductionmentioning
confidence: 99%
“…The electrostatic repulsion of these nanoparticles prevents the formation of a dense stabilizing layer on the oil/water interface. To neutralize this effect, several approaches are used, including the chemical modification of the cellulose nanocrystal surface , and the addition of electrolytes , or oppositely charged particles. , In our previous work, we showed that rod-like CNCs with partially acetylated surfaces have a higher emulsifying ability than sulfated CNC, allowing a reduction of the concentration of electrolyte and the avoided usage of other additives. Therefore, the utilization of acetylated CNC has more prospects in emulsion design.…”
Section: Introductionmentioning
confidence: 99%